Simulated fire injury: effects of trunk girdling and partial defoliation on reproductive development of apple trees (Malus domestica) - Gerhard C. Rossouw; Oluyoye Idowu; Aphrika Gregson; Bruno P. Holzapfel (Trees, 2024)
Fire damage can significantly impact fruit productivity in orchards. However, the effects of nonlethal fire injuries on the reproductive development of apple trees remain poorly understood. To investigate these effects, we implemented three treatments: trunk girdling to simulate fire injury to xylem, defoliation of a third of the canopy (simulated crown fire injury), and a combined treatment (simulated surface fire injury), alongside a control. The experiment was conducted during the 2021–22 growing season using a randomised block design with four biological replicate plots. Girdling was less effective than crown and surface fire treatments in influencing fruit composition during the current growing season, and flowering and fruiting in the following season. The crown and surface fire treatments induced localised detrimental effects on fruit sugar and titratable acidity while stimulating peel blush. Additionally, these treatments led to reduced starch reserves by harvest, which likely disrupted subsequent flowering and crop load near the previously defoliated sections of the canopy. When surface fires damage leaves near the base of the canopy in addition to the trunk, fruit production in the lower part of the canopy is more likely to be compromised in the following season. Crown fires, which cause leaf loss near the apex of the canopy, appear to be particularly detrimental to tree productivity, as the top defoliation treatment impaired carbohydrate reserves in shoot terminals and roots. In conclusion, fire-induced loss of leaf area during fruit growth alters fruit composition in the current growing season and may lead to lower yields in the subsequent season.